PENERAPAN REALISTIC MATHEMATICS EDUCATION DI SITUS PATIRTAAN NGAWONGGO: STUDI KASUS PENINGKATAN KEMAMPUAN STATISTIKA - Badi'atu Sholihah; Sari, Maya Novita; Izzah, Nadia Adilatul; Sunarko, Wulandari; Dewi, Riska Mustika; Sumitro, Nopem Kusumaningtyas (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2025)
This study aims to describe the improvement of sixth-grade elementary students’ basic statistical abilities through the Realistic Mathematics Education (RME) approach based on local cultural context. The learning location was purposively selected at Patirtaan Ngawonggo Site, a historical place in Malang Regency that offers a natural atmosphere and authentic learning experiences. This research employed a mixed-method approach with an exploratory case study design, focusing on both the process and outcomes of contextual learning. Qualitative data were collected through observation, field notes, documentation, and reflective interviews, while quantitative data were obtained from students’ pre-test and post-test results on basic statistics. Data analysis utilized two techniques: qualitative descriptive analysis to interpret the contextual learning process, and simple descriptive statistics to compare the mean scores of students’ pre-test and post-test results. The findings revealed that students’ direct engagement in contextual learning within a local cultural environment significantly contributed to the enhancement of their understanding of basic statistical concepts, including mean, median, and mode. The average pre-test score of 58.5 increased to 90 in the post-test, indicating an improvement of 53.85%. In addition to cognitive gains, students also demonstrated higher enthusiasm, focus, and reflective awareness of the relevance of statistics in daily life. Thus, the implementation of the RME approach in the cultural setting of Patirtaan Ngawonggo proved to be effective in meaningfully improving students’ basic statistical skills, while simultaneously strengthening the integration of mathematics learning with local cultural preservation.